Affirming diversity through reading - Posada Ortiz, Julia Zoraida (Colombian Applied Linguistics Journal, 2004)
In this article I will summarize a small scale project carried out at a private university in Bogotá, with eight undergraduate students. The project aimed at finding out what their oral discourse informed me about their beliefs regarding gender and ethnicity. It also had two other purposes: First, to give the students the opportunity to reflect upon the complexity of the world we live in and the many perspectives involved in this complexity and second, to make students active participants in a democratic society. To achieve these goals a selection of texts written by non-canonical, female and Afro-American writers was given to the students. I conducted five informal interviews, which were audio-taped. The analysis of the responses given by the students showed that there is an internalisation of the values which characterises the Western society we live in. A society ruled by dichotomies such as male/female, white/black and rich/poor, who perpetuate power relations that favor certain groups over others. The students became active participants by becoming more critical and making decisions about how to improve further editions of the textbook they currently use and suggesting the editors to create a more inclusive book.